MARKETING INCENTIVES AND MARKETING TEAM COOPERATION ON JOB SATISFACTION AND IMPLICATIONS TO THE EMPLOYEES - Afif Afandi; Muhammad Suparmoko; Ade Manggala Hardianto (International Journal of Economy, Education and Entrepreneurship, 2022)
This research used a survey approach to describe the opinions of respondents and the link between variables. The study aimed to improve employee performance by focusing on how Employees are more likely to work hard toward organizational goals if they enjoy what they do for a living. The Structural Equation Model with the Partial Least Square (PLS) approach is the statistical tool utilized in this study. According to the research findings, job satisfaction can moderate the effect of incentives on the Performance of employees. The initial sample value of the coefficient intervals calculates to be 0.440, and the T statistic value was determined to be 2.297, which was higher than the T table value of 1.96. The P values ranged from 0.02 to 0.05. The connection between the effect of teamwork and job contentment can mediate by job satisfaction. Regarding the Performance of the workforce, the original sample coefficient of intervals comes in at 0.252, with a T statistic that reads 2: 174 > T table 1.96 and P values that range from 0.03 to 0.05